Response of the Flat Reinforced Concrete Floor Slab with Openings under Cyclic In-Plane Loading - Eden Shukri Kalib; Yohannes Werkina Shewalul (Advances in Civil Engineering)
The responses of flat reinforced concrete (RC) floor slabs with openings subjected to horizontal in-plane cyclic loads in addition to vertical service loads were investigated using nonlinear finite element analysis (FEA). A finite element model (FEM) was designed to perform a parametric analysis. The effects of opening sizes (7%, 14%, 25%, and 30% of the total area of the slab), opening shapes (elliptical, circular, L-shaped, T-shaped, cross, and rectangular), and location on the hysteretic behavior of the floor slab were considered. The research indicated that openings in RC floor slabs reduce the energy absorption capacity and stiffness of the floor slab. The inclusion of 30% opening on the floor slab causes a 68.5%, 47.3%, and 45.6% drop in lateral load capacity, stiffness, and lateral displacement, respectively, compared to the floor slab with no openings. The flat RC floor slab with a circular opening shape has increased efficiency. The placement of the openings is more desirable by positioning the openings at the intersection of two-column strips.